Iowa RBA, May 1, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa RBA update for May 1, 1995. Highlights of the update include sightings of the continued presence of a Fish Crow, two Bewick's Wrens, Long-tailed Duck, Yellow Rail, and several species of warblers. Also included are handwritten notes for the next week's update with sightings of three Great-tailed Grackles and Long-billed Dowitchers. Epson - sheet feed/flatbed